A new media approach: visualisation of a digital exhibition. A case of study. (25th November 2008) - Acuna, Blanca
This paper addresses the framework for a design case study of a digital application. The digital interface will be developed for the main archaeological collection of a museum in Mexico. The purpose of the research project "a new media approach: visualisation of a digital exhibition", is to reflect on the importance that information design, navigation structures, and interactivity have in the design of interfaces within the digital domain.